Kualitas Pelayanan Mempengaruhi Jumlah Kunjungan Tamu Di Restoran Nom Nom Nom - Nuryadina Augus Rini (Jurnal Sains Terapan Pariwisata, 2020)
The purpose of this research is to analyze the quality of service to the number of guests in NOM NOM NOM Restaurant. In addition to analyze the quality of service, this research is also to find the valid data for the problems solving found to influence of quality of service to increase the number of guests in Nom Nom Nom Restaurant. There are some problems found related with the discussion of this research, such as there is a significant influences impact on the quality services the number of visitors in a Nom Nom Nom Restaurant, how much is the influences found that have had on the quality of services for the visitors at Nom Nom Nom Restaurant, and how to improve the quality of services in a Nom Nom Nom Restaurant. The methods used in this study are quantitative descriptive. The population in this research is the visitors of Nom Nom Nom Restaurant. Sampling used is the technique of Likert scale amounted to 100 people. The data analysis technique used is a simple linear regression analysis technique. The conclusion of this research on quality of service has positive effect on increasing number of guests.